Eggshell depigmentation in the late phase of production is associated with altered Microbiota and Metabolism of the uterus in laying hens - Dai, Dong; Gao, Libing; Pan, Yingli; Chen, Chaojiang; Ma, Kaixuan; Zhang, Haijun; Wu, Shugeng; Qi, Guanghai; Wang, Jing (Poultry science, 2025)
The significant depigmentation of brown eggshells occurs in the in the late-phase laying hens, which directly affects consumer acceptance. However, the biological mechanism of eggshell depigmentation based on uterine metabolism has not been elucidated. In this study, a total of 4 group were as follows: 1) 65-week-old laying hens with normal color; 2) 65-week-old laying hens with light color; 3) 80-week-old laying hens with normal color; 4) 80-week-old laying hens with light color. Variations in the pigment contents, uterine antioxidant capacity, uterine microbiota, and uterine metabolomics were examined in current study. Results showed that significantly decreased L* values and increased a* and b* values were observed in the depigmentation group (P < 0.05). The protoporphyrin IX content of the uterus with eggshell depigmentation was significantly decreased in 65-week-old laying hens (P < 0.05). Uterine MDA content was significantly increased in the depigmentation groups at 65 and 80 weeks of age, accompanied by reduced SOD and increased IgA levels (P > 0.05). The abundance of Proteobacteria and Campilobacterota was markedly reduced in the uterus with eggshell depigmentation, whereas Firmicutes was elevated at 65 weeks of age (P < 0.05). Further, Psychrobacte as biomarkers can accurately distinguish between normal color and depigmentation in eggshells (AUC = 0.91). A total of 51 differential metabolites were significantly enriched in the down-regulated sphingolipid metabolism, linoleic acid metabolism, citrate cycle, oxidative phosphorylation, PPAR signaling pathway, FoxO signaling pathway, and apoptosis at 65 weeks of age (P < 0.05). Meanwhile, there were 82 differential metabolites were significantly up-regulated at 80 weeks of age, which mainly enriched in up-regulated linoleic acid metabolism, purine metabolism, and pentose phosphate pathway (P < 0.05). These findings elucidate the specific metabolic mechanisms responsible for eggshell depigmentation in 65- and 80-week-old laying hens, contributing to the improvement of eggshell depigmentation by the precise nutritional modulation in the late-phase laying hens.